The Time of Their Lives : Nurturing Babies' Learning and Development in Early Childhood Settings. - French, Geraldine (Barnardo's, Ireland, 2018)
This book provides an understanding of theory, coupled with practical strategies, to enhance the learning and development of babies responsively, respectfully and sensitively in early childhood settings.